Four new species of Tanycarpa (Hymenoptera, Braconidae, Alysiinae) from the Palaearctic Region and new records of species from China - Yao, Junli; Kula, Robert R.; Wharton, Robert A. (Zootaxa, 2015)
Four new species of Tanycarpa (Hymenoptera, Braconidae, Alysiinae), T. gymnonotum Yao sp. n., T. similis Yao sp. n., T. areolata Yao sp. n., and T. lineata Yao sp. n., are described from the Palaearctic Region of China, and T. chors Belokobylskij is newly recorded from China. Significant range extensions are given for T. bicolor (Nees von Esenbeck), T. gracilicornis (Nees von Esenbeck), and T. mitis Stelfox. A key to the Palaearctic species of Tanycarpa is provided.